2016
DOI: 10.1111/jcpt.12482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic variations in the genes encoding NOD1 and NOD2 on type 2 diabetes mellitus and insulin resistance

Abstract: This study is the first to look for possible association of the genotype frequencies of NOD1 and NOD2 genes with T2DM and IR. The significant finding of this report is that the rs5743336 and rs2066847 variations in the NOD1/2 gene are not associated with T2DM and IR risk in patients of Turkish origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…Decreased NOD-like signaling in human fibroblast cells with HG stress were also observed in a previous study (12). Furthermore, genetic variation of NOD1 and NOD2 has been associated with type II DM (23), suggesting the importance of NOD-like signaling in DM-mediated stress. Previous results have suggested that ECM remodeling is important for wound repair, which is in agreement with previous findings (24).…”
Section: Discussionsupporting
confidence: 77%
“…Decreased NOD-like signaling in human fibroblast cells with HG stress were also observed in a previous study (12). Furthermore, genetic variation of NOD1 and NOD2 has been associated with type II DM (23), suggesting the importance of NOD-like signaling in DM-mediated stress. Previous results have suggested that ECM remodeling is important for wound repair, which is in agreement with previous findings (24).…”
Section: Discussionsupporting
confidence: 77%
“…The NOD2 gene has been related to inflammation, since a higher expression of NOD2 may contribute to an increased inflammatory response of immune cells in diet-induced obesity [54]. Genetic variants of NOD2 may also influence the risk of chronic inflammation, insulin resistance, and T2D [55]. The gene FPR2 binds to lipid mediators such as resolvin D1 for promoting resolution of inflammation [56], including the resolution of obesity-induced chronic low-grade inflammation [57].…”
Section: Discussionmentioning
confidence: 99%
“…Inwiefern NOD1 und NOD2 einen genetischen Beitrag zur Fettleibigkeit beim Menschen leisten, ist derzeit nicht bekannt. Gut untersuchte Mutationen, wie der mit Morbus Crohn assoziierte L1008fs-Polymorphismus in NOD2 und der E266K-Austausch in NOD1, scheinen nicht mit T2DM und einer IR assoziiert [53]. Eine Arbeit lässt jedoch eine Assoziation eines Polymorphismus in NOD1 (Glu266Lys) mit der Aufnahme gesättigter Fettsäuren aus der Nahrung und der Insulinsensitivität vermuten [54].…”
Section: Nod1 Und Nod2unclassified